2023
DOI: 10.1021/acs.orglett.3c01502
|View full text |Cite
|
Sign up to set email alerts
|

N-Aminoglycine and Its Derivatives Stabilize PPII Secondary Structure

Abstract: The identification of unnatural residues that stabilize polyproline type 2 (PPII) folds can aid in the design of peptidomimetics targeting PPII-binding domains. Here, we examine the impact of peptide backbone N-amination on PPII helix stability and find N-aminoglycine (aGly) to be an effective PPII promoter. Further derivatization of an aGly-containing peptide affords N′-alkylated analogues with increased helical propensity. Backbone N-amination of glycine represents a convenient approach to stabilize PPII con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Additionally, the electron-withdrawing hydrazide N′H 2 group lowers the amide rotational barrier, enhances carbonyl electrophilicity, and therefore lowers the π* CO LUMO energy . Consistent with these characteristics, we found that the incorporation of aGly into a host–guest model peptide enhanced PPII helicity and thermal stability relative to those of both Gly and Pro, as measured by CD (Figure B,C) . In contrast, the PPII fold was severely disrupted when the Cα-substituted aAla was incorporated as the guest residue.…”
Section: Peptide N-amination In Other Foldsmentioning
confidence: 80%
See 2 more Smart Citations
“…Additionally, the electron-withdrawing hydrazide N′H 2 group lowers the amide rotational barrier, enhances carbonyl electrophilicity, and therefore lowers the π* CO LUMO energy . Consistent with these characteristics, we found that the incorporation of aGly into a host–guest model peptide enhanced PPII helicity and thermal stability relative to those of both Gly and Pro, as measured by CD (Figure B,C) . In contrast, the PPII fold was severely disrupted when the Cα-substituted aAla was incorporated as the guest residue.…”
Section: Peptide N-amination In Other Foldsmentioning
confidence: 80%
“…R. Rajewski, B. H. Wright, M. M. Gerrein, T. A. Del Valle, J. R. 10.1021/acs.orglett.3c01502Org. Lett.20232543664370 …”
Section: Key Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to lactam cross-linked variants, the trans -2-butenyl cross-linked variant 19 has lower cross-linker hydrophobicity overall and displayed no apparent digestion within 4 h. These data suggest that stability to trypsin proteolysis is independent of EphB2 receptor inhibitory potency. Improvements in proteolytic stability are thus potentially achievable with amide modification, such as N-alkylation or N-amination. , …”
Section: Resultsmentioning
confidence: 99%
“…The core principle of our approach was to introduce a cross-linker to stabilize the receptor-bound peptide structure in a similar fashion to previous studies. Specifically, we sought to stabilize the polyproline II helix structure at the C-terminus of SNEW. Factors influencing polyproline II helix stability have been studied extensively in proline-rich peptides, including several examples of cross-linking. Complementary to these studies, we used the wealth of existing knowledge about cross-linking of peptide α-helices to rationally guide the screening of cross-linkers for stabilization of a single turn of the C-terminal polyproline II helical segment of SNEW . Through design, synthesis, and evaluation of a collection of SNEW variants, we identified variants that are more potent than SNEW in inhibiting the EphB2–ephrin B2 interaction.…”
Section: Introductionmentioning
confidence: 99%